Real Exchange Rate Volatility : Does the Nominal Exchange Rate Regime Matter? - Liang, Hong (IMF Working Papers; Working Paper ;, 1998)
A recent study by Grilli and Kaminsky (1991) argues that real exchange rate (RER) behavior is likely to be dependent on the particular historical period rather than on the nominal exchange rate arrangement itself. This paper reexamines RER behavior using alternative data sets, as well as different econometric methods, over the period 1880-1997. It finds strong evidence supporting the nonneutrality hypothesis of nominal exchange regime on RER volatility. Also, regime shifts play an important role in determining the persistence of shocks to the RER.